Pelatihan Penggunaan Mesin Penggoreng Amplang untuk Meningkatkan Produktivitas dan Kualitas Bagi Masyarakat Loa Janan Ilir Kota Samarinda - Imam; Lolongan, Samen; Sihombing, Ruspita (Jurnal ETAM, 2025)
The process of frying amplang crackers is done manually. In this way, the amplang often burns, so some have to be thrown away. The purpose of engineering this tool is to overcome the problem of burning that occurs during the frying process. This service method is carried out by identifying working drawings, manufacturing, initial testing and tool performance testing. Performance testing involves weighing the dough and then putting the dough into a frying pan filled with heated cooking oil, after which the driving motor is turned on to stir the amplang and the frying time is recorded. After the amplang is cooked, the amplang is removed from the pan and weighed. This was repeated four (4) times as well as visual observations. The test results can be concluded that the tool can overcome burning because the stirring is carried out by an electric motor so that it is even and the mixture does not come into direct contact with the outer pan which is in contact with the heat source. The flour that is on the surface of the dough when frying falls into the outer pan so it doesn't dirty the surface of the amplang. Fryer capacity 12 kg/batch. Yield 70%. The average time for frying amplang is 35 minutes. The stirring speed can be adjusted over a wide range from 30 rpm to 52.5 rpm without causing the amplang to come out of the pan.